Nickel-catalyzed electrochemical reductive relay cross-coupling of alkyl halides with alkyl carboxylic acids. Issue 23 (18th October 2021) - Jiao, Ke-Jin; Ma, Cong; Liu, Dong; Qiu, Hui; Cheng, Bin; Mei, Tian-Sheng
Abstract : A highly regioselective Ni-catalyzed electrochemical (undivided cell) reductive relay cross-coupling between alkyl carboxylic acids and alkyl bromides has been developed. Abstract : A highly regioselective Ni-catalyzed electrochemical (undivided cell) reductive relay cross-coupling between alkyl carboxylic acids and alkyl bromides has been developed. This strategy allows the direct acylation of benzylic C(sp 3 )–H bonds in good yields from commercially available alkyl carboxylic acids, thus providing an alternative strategy for the synthesis of dialkyl ketones. Various functional groups are tolerated under mild reaction conditions.